Reduction in the Treatment Gap for Breast Cancer in Mexico under Seguro Popular, 2007 to 2016. Issue 1 (1st January 2022) - Unger-Saldaña, Karla; Contreras-Manzano, Alejandra; Lamadrid-Figueroa, Héctor; Mohar, Alejandro; Suazo-Zepeda, Erick; Espinosa-Tamez, Priscilla; Lajous, Martin; Reich, Michael R.
ABSTRACT: As Mexico's government restructures the health system, a comprehensive assessment of Seguro Popular's Fund for Protection against Catastrophic Expenses (FPGC) can help inform decision makers to improve breast cancer outcomes and health system performance. This study aimed to estimate the treatment gap for breast cancer patients treated under FPGC and assess changes in this gap between 2007 (when coverage started for breast cancer treatment) and 2016. We used a nationwide administrative claims database for patients whose breast cancer treatment was financed by FPGC in this period (56, 847 women), Global Burden of Disease breast cancer incidence estimates, and other databases to estimate the population not covered by social security. We compared the observed number of patients who received treatment under FPGC to the expected number of breast cancer cases among women not covered by social security to estimate the treatment gap. Nationwide, the treatment gap was reduced by more than half: from 0.71, 95% CI (0.69, 0.73) in 2007 to 0.15, 95%CI (0.09, 0.22) in 2016. Reductions were observed across all states . This is the first study to assess the treatment gap for breast cancer patients covered under Seguro Popular . Expanded financing through FPGC sharply increased access to treatment for breast cancer. This was an important step toward improving breast cancer care, but high mortality remains a problem in Mexico. Increased access to treatment needs to be coupled with effective interventions to assure earlier cancer diagnosis and earlier initiation of high-quality treatment.